MERCURY METHYLATION INFLUENCED BY AREAS OF PAST MERCURY MINING IN THE TERLINGUA DISTRICT, SOUTHWEST TEXAS, USA - Gray J.E.; Hines M.E.; Biester H. (My University, 2006)
Speciation and microbial transformation of Hg was studied in mine waste from abandoned Hg mines in SW Texas to evaluate the potential for methyl-Hg production and degradation in mine wastes. In mine waste samples, total Hg, ionic Hg2+, Hg0, methyl-Hg, organic C, and total S concentrations were measured, various Hg compounds were identified using thermal desorption pyrolysis, and potential rates of Hg methylation and methyl-Hg demethylation were determined using isotopic-tracer methods. These data are the first reported for Hg mines in this region. Total Hg and methyl-Hg concentrations were also determined in stream sediment collected downstream from two of the mines to evaluate transport of Hg and methylation in surrounding ecosystems. Mine waste contains total Hg and methyl-Hg concentrations as high as 19,000 μg/g and 1500 ng/g, respectively, which are among the highest concentrations reported at Hg mines worldwide. Pyrolysis analyses show that mine waste contains variable amounts of cinnabar, metacinnabar, Hg0, and Hg sorbed onto particles. Methyl-Hg concentrations in mine waste correlate positively with ionic Hg2+, organic C, and total S, which are geochemical parameters that influence processes of Hg cycling and methylation. Net methylation rates were as high as 11,000 ng/g/day, indicating significant microbial Hg methylation at some sites, especially in samples collected inside retorts. Microbially-mediated methyl-Hg demethylation was also observed in many samples, but where both methylation and demethylation were found, the potential rate of methylation was faster. Total Hg concentrations in stream sediment samples were generally below the probable effect concentration of 1.06 μg/g, the Hg concentration above which harmful effects are likely to be observed in sediment dwelling organisms; whereas total Hg concentrations in mine waste samples were found to exceed this concentration, although this is a sediment quality guideline and is not directly applicable to mine waste. Although total Hg and methyl-Hg concentrations are locally high in some mine waste samples, little Hg appears to be exported from these Hg mines in stream sediment primarily due to the arid climate and lack of precipitation and mine runoff in this region. © 2006 Elsevier Ltd. All rights reserved.